CAPITAL FINANCING OF RUSSIAN COMPANIES IN GLOBAL TURBULENCE - S. Tshurina (Управленческие науки)
The country’s economic development is connected with the necessity of companies’ capital financing. In global turbulent period the significant importance is given to the state support of economic real sector. Government regulation of the economy must be aimed at the generating conditions of companies’ effective usage the available resources, at constant renewal the fi ed assets, searching for the new methods of capital fi While capital fi the companies should reasonably combine internal reserves i.e. amortization and profit, with any other sources of financing means, the banks’ credits and budget financing in particular. Russian real economic sector needs in state support directed at encouraging the domestic production and manufacturing. A state must thoughtfully react to the changes in economy and take measures allowing the national business to overcome the economic shocks and build up the constructive dialogue with the representatives of the economic real sector.